The impact of recent Covid-19 infection on cytomegalovirus antibodies - Wang Dan; Xu Yuzhu; Wen Han; Li Laisheng; Fan Jinjin; Liu Min; Chen Wei; Wang Xin (Journal of Infection and Public Health, 2025)
Background: The COVID-19 pandemic has led to an unexpected rise in patients with increased CMV-IgM antibody titers at our hospital in China, without concurrent evidence of CMV-related organ pathology, prompting an investigation into the relationship between CMV-IgM and COVID-19. Methods: We retrospectively analyzed 516 patients tested for CMV-IgG or IgM between January 15 and February 3, 2023. We used Mann-Whitney U and chi-square tests to compare COV2-IgG/IgM profiles between CMV-IgM positive and negative groups. Logistic regression assessed risk factors for increased CMV IgM positivity, adjusting for age, gender, CRP, and CMV IgG. CMV DNA was detected by real-time PCR (detection limit >500 copies/mL), and CMV-IgG/IgM and COV2-IgG/IgM titers were measured by ELISA. Variance analysis compared CRP levels across groups. Results: A notable rise in CMV IgM positivity was observed following the COVID-19 outbreak. The group of patients testing positive for CMV IgM exhibited significantly higher titers of COV2 IgM (0.83 vs 0.49, P < 0.001) and a higher rate of COV2 IgG positivity (93.8 % vs 85.4 %, P = 0.02). Logistic regression analysis demonstrated a significant association between the COV2-IgG and an increased likelihood of CMV IgM positivity (OR=3.050, 95 % CI=1.208–7.700, P = 0.018). A linear correlation was identified between CMV IgM and COV2 IgM titers. CMV IgM levels did not differ based on CMV DNA status, and no association was observed between CRP values and CMV IgM positivity. These findings suggest that the increase in CMV IgM is likely attributable to COVID-19 rather than an active CMV infection. Conclusions: Our research indicates that increased CMV IgM levels may correlate with COVID-19, possibly due to antibody cross-reactivity. Caution is advised when interpreting CMV IgM results amidst the pandemic. Using CRP as a supplementary marker may aid in identifying active infections. It's crucial to consider COVID-19's impact on CMV IgM levels in clinical assessments.